AquaNet - Automatic sensors from Erken AquaNet platform - Erken Laboratory (Uppsala University, 2024)
Automatic sensor data from the AquaNet mesocosm facility.
Erken Laboratory (2024). AquaNet - Automatic sensors from Erken AquaNet platform, 2022-07-07–2022-08-12 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/mWdvF9JHBQUywC2DHXNd5iIQ
Keywords: SITES AquaNet; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap